Hypersynchrony in sarcomeric hypertrophic cardiomyopathy: description and mechanistic approach using multimodal electro-mechanical non-invasive cartography (HSYNC study) - Réant, Patricia; Bonnet, Guillaume; Dubé, Frédérique; Massie, Charles; Reynaud, Amélie; Michaud, Matthieu; Duchateau, Josselin; Lafitte, Stéphane (Frontiers in Cardiovascular Medicine, 2024)
Background: Little is known about left ventricular (LV) sequences of contraction and electrical activation in hypertrophic cardiomyopathy (HCM). A better understanding of the underlying relation between mechanical and electrical activation may allow the identification of predictive response criteria to right ventricular DDD pacing in obstructive patients. Objective: To describe LV mechanical and electrical activation sequences in HCM patients compared to controls. Materials and methods: We prospectively studied, in 40 HCM patients (20 obstructive and 20 non-obstructive) and 20 healthy controls: 1) mechanical activation using echocardiography at rest and cardiac magnetic resonance imaging, 2) electrical activation using 3-dimensional electroca¬rdiographic mapping (ECM). Results: In echocardiography, healthy controls had a physiological apex-to-base delay (ABD) during contraction (23.8±16.2ms). Among the 40 HCM patients, 18 HCM patients presented a loss of this ABD (<10ms, defining hypersynchrony) more frequently than controls (45% vs. 5%, p=0.017). These patients had a lower LV end-diastolic volume (71.4±9.7ml/m2 vs. 82.4±14.8ml/m2, p=0.01), lower native T1 values (988±32ms vs. 1028±39ms, p=0.001) and tended to have lower LV mass (80.7±23.7g/m2 vs. 94.5±25.3g/m2, p=0.08) compared with HCM patients that had a physiological contraction sequence. There was no significant relation between ABD and LV outflow tract obstruction. While HCM patients with a physiological contraction sequence presented an ECM close to those encountered in controls, patients with a loss of ABD presented a particular pattern of ECM with the first potential more frequently occurring in the postero-basal region. Conclusion: The LV contraction sequence can be modified in HCM patients, with a loss of the physiological ABD, and is associated with smaller LV dimensions and a particular pattern of ECM. Further research is needed to determine whether this pattern is related to an electrical substrate or is the consequence of the hypertrophied heart’s specific geometry.